Exposure to low-dose ionising radiation from cardiac catheterisation and risk of cancer: the COCCINELLE study cohort profile - Damien Bonnet; Claire Dauphin; Stéphanie Douchin; Sarah Cohen; Estelle Rage; Clément Karsenty; Jean-Benoît Thambo; FRANCOIS GODART; Klervi Leuraud; Marie-Odile Bernier; Caroline Ovaert; Jean-François Piéchaud; et al. (BMJ Open)
Purpose The COCCINELLE study is a nationwide retrospective French cohort set up to evaluate the risk of cancer in patients who undergone cardiac catheterisation (CC) procedures for diagnosis or treatment of congenital heart disease during childhood.Participants Children who undergone CC procedures from 1 January 2000 to 31 December 2013, before the age of 16 in one of the 15 paediatric cardiology departments which perform paediatric CC in mainland France were included. The follow-up started at the date of the first recorded CC procedure until the exit date, that is, the date of death, the date of first cancer diagnosis, the date of the 18th birthday or the 31 December 2015, whichever occurred first. The cohort was linked to the National Childhood Cancer Registry to identify patients diagnosed with cancer and with the French National Directory for the Identification of Natural Persons to retrieve the patients’ vital status.Findings to date A total of 17 104 children were included in the cohort and followed for 110 335 person-years, with 22 227 CC procedures collected. Among the patients, 81.6% received only one procedure. Fifty-nine cancer cases were observed in the cohort. Standardised incidence ratios (SIRs) were increased for all-cancer (SIR=3.8, 95% CI: 2.9 to 4.9), leukaemia (SIR=3.3, 95% CI: 2.0 to 5.4), lymphoma (SIR=14.9, 95% CI: 9.9 to 22.5) and solid cancers excluding central nervous system (CNS) tumours (SIR=3.3, 95% CI: 2.0 to 5.5) compared with the general population.Future plans Dose reconstruction is currently underway to estimate individual cumulative doses absorbed to relevant organs, including red bone marrow and brain for respectively haematologic disorders and CNS tumours risk estimation. A dose–response analysis will be conducted with consideration to confounding factors such as age at exposure, gender, predisposing factors to cancer and other sources of medical diagnostic low-dose ionising radiation.